(untitled) (TAMADDUN NURI JURNALI, 2024)
The article provides a scientific basis for the concept of information warfare, its ideological nature and ideological features. Since globalization processes and information society trends have a negative impact on people’s consciousness in every region, an important task is to eliminate it and enhance its positive impact. It is impossible to adapt to this phenomenon without studying it deeply and, if necessary, changing its direction accordingly. Failure to thoroughly study the threats in the modern global world, failure to develop a strategy, tactics and technologies for their elimination are equivalent to surrendering the country’s economy, culture and spirituality to a torrential flood from the mountains or a sea typhoon.